Flood early warning for early action—evacuation and transfer: case of Shouchang Town, Zhejiang Province, China - Musyoka, Wellington W.; Jun, Wang; Mwanthi, Anthony M.; Kiarii, Ruth W. (Frontiers in Water, 2025)
Flooding in riverine basins remains a recurring disaster, often leading to extensive property destruction and, in extreme scenarios, loss of lives. In recent years, the Shouchang River Basin in Zhejiang Province, China, has experienced increasing flood risks, driven by a combination of extreme weather events, urban expansion, and alterations in natural land use. Managing these events is becoming increasingly crucial to minimize the impact on vulnerable communities and critical infrastructure. This study develops an integrated framework for flood forecasting and hydrodynamic floodplain mapping using HEC-HMS and HEC-RAS 6.5 over a 10 km stretch of the Shouchang River upstream of Shouchang Town. The hydrological model (HEC-HMS) simulates rainfall-runoff processes across five sub-basins, using observed rainfall and streamflow data from four gauging stations, to capture key flow dynamics. Based on local plans for Shouchang Town, a total of 28 villages are situated within exposure areas of sub-basin 5. Out of villages only 22 rescue centers are found to be unaffected and thus effective for sheltering flood victims. Four rescue centers, Yongjiaqiao, Henanli, Ximen, and Datanbian would need relocation to higher grounds, including adding new resettlement sites and modifying transfer plans and routes. Simulations show that, while flood defenses protect most regions under upstream flows of 1,200 m3/s, the levees along Shili Shouchngjiang Ecology Leisure Greenway breach once this threshold is surpassed. The study highlights the need to review the existing flood evacuation and transfer analysis system, given that some evacuation centers could be exposed to flood associated risks.